Service Quality and Customer Satisfaction: Halal Certificate Application in Malaysia / Mariam Setapa...[et al.] - Setapa, Mariam; Kamarul Zaman, Liziana; Wan Mustapha, Wan Asma Hanim; Mohd Kanafiah, Siti Farah Haryatie; Mohd Noor, Nor Raihana Asmar (Universiti Teknologi MARA Cawangan Kelantan, 2020)
In order to achieve a global scale of economic growth, products or services must comply with standards and requirements that will enable them to be recognised as halal and safe for consumption. As a halal certificate provider, the Islamic Development Department of Malaysia (JAKIM) at the national level, or Jabatan Hal Ehwal Agama Islam Kelantan (JHEAIK) at the state level, is responsible for granting and certifying halal certification for applicants within a specified period. Serving and dealing with applicants or customers require some skills and knowledge because it is a part of their role in the service sector. Thus, this paper intends to study customer satisfaction during halal certificate application, and the respondents came from various backgrounds of businesses. Data were gathered from 77 respondents who attended a course organised by JHEAIK and were analysed using SmartPLS 3.2.1 software. The result suggests that tangibles and reliability determine customer satisfaction during halal certificate application, while responsiveness was not a factor in determining satisfaction among customers.